1979
DOI: 10.1038/ki.1979.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of para-aminohippurate on renal transport of oxalate

Abstract: The renal handlinig of oxalate was examinied by free-flow micropuncture, intratubular microinijectioni, an(d droplet precessioni techniques in the rat. After the stustained i.v. infusionj of [14C]oxalate, the fractional (Ieliverv of oxalate from the early portions of the proximal tul)ule was 120.1+4.4%, indicating net secretioin. Fractionial delivery rates from the late proximal tubtule (124.6+6.1), distal tubule (120.9+2.9), and final urine (126.2+2.9%) were not different froml that of the early proximal tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…For comparison, data of distal punc tures and of ipsilateral urine are included. It is apparent that fractional recovery of uC-oxalate increases along the proximal convolution and exceeds unity by some 10% at the end of this segment, thus in dicating proximal net secretion of oxalate and confirming previous reports [13,20], At present we favor the view that net secre tion of oxalate occurs in the proximal tubule probably including the pars recta. The ab solute values of the net secretion of oxalate found in the anesthetized rat, however, are of little importance since the secretion might well be influenced by the anesthesia itself, by the state of hydration [5] and by several other factors.…”
Section: Proximal Bidirectional Transportsupporting
confidence: 78%
See 2 more Smart Citations
“…For comparison, data of distal punc tures and of ipsilateral urine are included. It is apparent that fractional recovery of uC-oxalate increases along the proximal convolution and exceeds unity by some 10% at the end of this segment, thus in dicating proximal net secretion of oxalate and confirming previous reports [13,20], At present we favor the view that net secre tion of oxalate occurs in the proximal tubule probably including the pars recta. The ab solute values of the net secretion of oxalate found in the anesthetized rat, however, are of little importance since the secretion might well be influenced by the anesthesia itself, by the state of hydration [5] and by several other factors.…”
Section: Proximal Bidirectional Transportsupporting
confidence: 78%
“…This led the authors to conclude that oxalate secretion is either limited to the late distal nephron or to nephron populations not accessible to usual micropuncture techniques. In contrast to this study, another group [13,20] showed proximal recoveries of oxalate significantly exceeding unity (1.2-1.3) and very similar values for the fractional excretion in urine. These data, therefore, were interpreted to indicate proximal net secretion of oxalate.…”
Section: Proximal Bidirectional Transportcontrasting
confidence: 44%
See 1 more Smart Citation
“…As demonstrated in dogs (132), humans (133), sheep (134), and rats (135), the bulk of body oxalate is excreted by kidneys, partially via glomerular fi ltration and partially via active secretion in the proximal parts of the nephron. In addition to secreting oxalate, proximal tubules are also sites of limited oxalate reabsorption (135,136), whereas the distal parts of a nephron are not involved in oxalate transport (137). Detailed studies on rat kidney proximal tubules indicated the presence of a low-affinity, high-capacity excretory system for o x a l a t e , w h i c h c a n b e i n h i b i t e d b y pchloromercuribenzoic acid (PCMB), cyanide, indacrinone (MK-196), furosemide, and paminohippurate (PAH) (137,138).…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 99%
“…In addition to secreting oxalate, proximal tubules are also sites of limited oxalate reabsorption (135,136), whereas the distal parts of a nephron are not involved in oxalate transport (137). Detailed studies on rat kidney proximal tubules indicated the presence of a low-affinity, high-capacity excretory system for o x a l a t e , w h i c h c a n b e i n h i b i t e d b y pchloromercuribenzoic acid (PCMB), cyanide, indacrinone (MK-196), furosemide, and paminohippurate (PAH) (137,138). However, these and other studies suggested that more than one secretory system, with different affi nities for oxalate, may be responsible for oxalate handling in mammalian kidneys (129, 137, and 138).…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 99%